On unit accentuation in Danish - and the distinction between deep and surface phonology - Rischel, Jørgen (Annual Report of the Institute of Phonetics University of Copenhagen, 1982)
This paper outlines a hierarchical model of stress in Danish with special emphasis on phrasal accentuation. The model is essentially based on impressionistic data and phonological and syntactico-semantic analysis of data representing the author's own usage. The relationship between prosody and syntax is explored, and it is suggested that there is an abstract prosodic structure which is very directly coupled to syntax, whereas this is not true of the hierarchical structure found in surface phonology. A considerable shrinkage of structure from deep phonology to (low distinctness levels of) surface phonology is assumed as part of the overall model.